Characteristics And Antibacterial Test Of Lactid Acid Bacteria From Sidoarjo Shrimp Petis Against Vibrio Sp, Bacteria - Intan Feby Nurhaliza; Kartika Dewi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Indonesia as the largest archipelago with abundant potential fishery resources contributes to national foreign exchange (Damayanti & Sugiarto, 2022). One of the main commodities of fishery products commonly exported by Indonesia is shrimp (Dewi et al., 2022). Increasing shrimp production through intensive aquaculture faces the challenge of disease, especially Vibrio sp. bacterial infection. The use of antibiotics as a general solution raises resistance problems, so alternatives such as probiotics are needed. Lactic acid bacteria (LAB) are potential candidates for probiotics because of their ability to produce organic acids that inhibit the growth of pathogenic bacteria. This study aims to analyse the characteristics of LAB from Sidoarjo shrimp petis, a typical fermented product that has potential as a source of LAB, and test its antibacterial ability against Vibrio sp. The stages carried out in the study consisted of 5 stages including the first stage of sampling, the second stage of lactic acid bacteria isolation, the third stage of characterisation of lactic acid bacteria isolates, the fourth stage of lactic acid bacteria antibacterial test, and the fifth stage of data analysis. The results showed the total colonies of Lactic Acid Bacteria (LAB) in the six isolates with a value of 7.08 x 106 colonies.mL. LAB characteristics on the six isolates consisted of macroscopic, microscopic, and biochemical characteristics. Microscopic characteristics of the six isolates showed the same results, namely round, white colour, flat and convex elevation, and smooth edges. Microscopic characteristics of the six isolates showed the same results, namely bacillus and gram-positive cell forms. Biochemical characteristics on the six isolates showed different results. Antibacterial tests were carried out after knowing the type of lactic acid bacteria isolates through several characteristic tests, it can be seen that there are 4 isolates including isolates PTS.5.1, PTS.5.2, PTS.6.1, and PTS. 6. 6. The results of antibacterial tests on 4 isolates have antibacterial compounds in inhibiting the growth of gram negative bacteria (Vibrio sp,). Seen the results obtained isolates that have the greatest antibacterial activity is PTS.5.1 with a final result of 10.2625 mm.